AVALIAÇÃO DA ESTABILIDADE DAS ALTERAÇÕES PROMOVIDAS PELO APARELHO REGULADOR DE FUNÇÃO FRÄNKEL-2 NOS ARCOS DENTÁRIOS - Tanaka, Tânia Gnecchi (2008)
This study analyzed the stability of occlusal alterations promoted by the Fränkel function regulator type 2 (FR-2), on a mean posttreatment period of 7.16 years. The study was conducted on 54 pairs of dental casts obtained from 18 patients with Class II division 1 malocclusion, with initial mean age of 10.77 years, treated with the RF-2 for 18 months and reevaluated after a mean period of 7.16 years. The dental casts were evaluated at treatment onset (T1), treatment completion (T2) and at 7.16 years after treatment (T3). Analysis comprised transverse and sagittal alterations, the Little irregularity index, as well as the treatment priority index (TPI). Changes occurring in the study periods were assessed by analysis of variance (ANOVA) followed by the Bonferroni test for multiple comparisons, at a significance level of 0.05. The results revealed that treatment with the FR-2 promoted a statistically significant transverse increase in both maxillary and mandibular arches; however, at the posttreatment period, there was partial or total relapse of this increase in most dimensions investigated. Maxillary and mandibular arch lengths were reduced throughout the study period. The Little irregularity index was stable during treatment, yet was increased at the posttreatment period. Moreover, treatment with the FR-2 provided a statistically significant decrease in the TPI, indicating the efficacy of treatment, which was stable at the posttreatment period. Therefore, the appliance FR-2 demonstrated to be effective for dental correction of Class II division 1 malocclusion, with stability of results at 7.16 years after treatment. However, with regard to the transverse increase in dental arches obtained during treatment, there was partial or total relapse of all variables analyzed.(AU)